Marketing Management Affecting Consumer Products Purchasing in Rueso District, Narathiwat Province - Abduldaning, Uwareeyoh (International Journal of Multidisciplinary in Management and Tourism, 2020)
This research aims to study marketing management and factors affecting consumer products purchasing in Rueso district, Narathiwat by using mixed methods. The data was collected by using questionnaire and in-depth interview that improved by three experts. The sample consisted of 10 retailers in the study area and the informants are the same group. The research found that 1) Most of the business owner or the business partner have planned the marketing system in order to achieve the business' objectives. Since selecting the right products for people in the study area. 2) Purchasing decisions of consumers depends on age, and purchasing date. In average of purchasing any consumer products, the person who takes part in making decision is customer's spouse.Frequency of purchasing and pay on each product in average. Person who takes part in decision making and traveling to purchase the product, depend on the education level about source and information, frequency of purchasing, frequent date of using service, average paying on each purchase, getting to the service, and reasons why not purchasing product. Consumer's purchasing decision depends on career and income. Reason why not purchasing products and customer's satisfaction of products and services also depend on number of family member, frequency of purchasing, and frequent date of purchasing. In addition, customer's satisfaction of products and services depend on the products, the price, and marketing strategy.